2020
DOI: 10.1001/jamadermatol.2020.1398
|View full text |Cite
|
Sign up to set email alerts
|

Association of Skin Psoriasis and Somatic Comorbidity With the Development of Psychiatric Illness in a Nationwide Swedish Study

Abstract: IMPORTANCEPsoriasis is a complex systemic disease with skin involvement, somatic comorbidity, and psychiatric illness (PI). Although this view of psoriasis is widely accepted, potential synergies within this triad of symptoms have not been adequately investigated.OBJECTIVES To investigate the independent association of skin psoriasis and somatic comorbidity with the development of PI and to assess whether skin psoriasis and somatic comorbidity act synergistically to produce a risk of PI that is greater than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In this study, the psoriasis group had a higher risk of suicidality, including suicidal ideation and suicide attempts, than that in the control group, but no significant difference was observed between the two groups regarding incidences of completed suicides. Our results suggest an association between psoriasis and suicidality, similar to that observed in previous cohort studies 12,24 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the psoriasis group had a higher risk of suicidality, including suicidal ideation and suicide attempts, than that in the control group, but no significant difference was observed between the two groups regarding incidences of completed suicides. Our results suggest an association between psoriasis and suicidality, similar to that observed in previous cohort studies 12,24 …”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest an association between psoriasis and suicidality, similar to that observed in previous cohort studies. 12,24 There exist conflicting study results regarding psoriasis and suicidality. Wu et al 25 reported that the risk of depression increased in patients with psoriasis and PsA, but that of suicidal ideation and suicide attempt did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…Suicidal patients may prioritize physical over mental health care because they consulted non–mental health care professionals twice as often as mental health professionals in the 30 days before death by suicide. Therefore, nonpsychiatric health care settings, especially primary care and emergency departments, are crucial for suicide risk screening …”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic‐inflammatory, immune‐mediated disease with typical erythematous, indurated, scaly, puritic, often painful skin plaques, affecting about 125 million people, worldwide (Korman, 2020). As underlying pathophysiology, an increased secretion of certain pro‐inflammatory cytokines have been proven, leading to a state of increased systemic inflammation and risk for numerous somatic comorbidities, for example, psoriatic arthritis, cardiovascular and metabolic diseases (Bu et al., 2022; Grozdev et al., 2014; Purzycka‐Bohdan et al., 2022), which in turn display independent and additional risk factors for mental comorbidities in psoriasis (Geale et al., 2020). In about every second to fifth patient, clinically relevant symptoms of anxiety and depression occur as major mental comorbidities (Dalgard et al., 2015; Pollo et al., 2021; Sondermann et al., 2021).…”
Section: Introductionmentioning
confidence: 99%